PENGARUH FAKTOR-FAKTOR KESULITAN BELAJAR TERHADAP PRESTASI BELAJAR - Maharani, Putri Kurnia (Fakultas Ekonomi, Universitas Negeri Semarang, 2009)
The objective of this research, to find out The Influences Difficulty Study of Internal and External Factor toward study achievement. Internal Factor consist of (Physiology, Intelligence, Talent, Interest, Motivation, Psichologycal weeknesses). External Factor consist of (Parents, Home Condition, Economic of Family, Teacher, Equipment, Building, Curriculum, Dicipline and time, mass media, social environment). Documentation and quessionaire are the instrument. The Data analyzis use descriptive dan inferensial statisthic. Population 133 student with proportional random sampling. And 58 samples.There is a positive influence between internal factor and external factor toward study achievement. Study Achievement has independent variable 55.1% dan remains 44.9% be explained by other variable. External Factor are the effective variable to influences study achievement, it can be shown from the Effective Contribution 29.2% and Relative Contribution 53%. Keywords : The Difficulty Study of InternalÃÂ Factor, Difficulty Study of Eksternal Factor , Study Achievement.